(untitled) (Journal of actual problems of jurisprudence, 2019)
The article analyzes the provisions of the new Convention on the legal status of the Caspian sea in 2018. It shows all the new novels, which are the fruit of more than 20 years of negotiations between representatives of the presidents of the Caspian States. The article identifies all the positive aspects of the Convention, as well as its shortcomings. The author, in general, positively assessed the efforts of the Caspian States on the harmonization of the «Constitution» of the Caspian sea, indicated that its adoption will have a positive impact in the life of the States surrounding the Caspian sea. In this Convention, the Caspian States in 24 articles developed a new Charter for the Caspian sea and agreed on a wide range of relations regarding the situation in the Caspian sea, in this case concerning the delimitation of the legal status of the water body, shipping, environmental protection, problems of safety of the whole sea, the region. Further, the Convention does not allow the presence of armed forces of other States in the Caspian sea. In terms of fisheries, the parties will determine the total allowable catch and allocate it to national quotas. The article notes that the Republic of Azerbaijan has been offering a fair «division» of the Caspian sea on the basis of international legal norms for many years. However, various artificial obstacles prevented the achievement of a final agreement on the status of the seas, and therefore the main advantage of the Convention on the legal status of the Caspian sea can be called the fact of its adoption, which is extremely important, because of this, of course, benefited all parties.